Drie eeue van militêre diensplig in Suid-Afrika - Meyers, E.M. (Scientia Militaria - South African Journal of Military Studies, 2012)
The history of National Service in South Africa goes back more than 300 years to the arrival of the first settlers at the Cape and the necessity to protect life and property. This was the start of the Commando system that the pioneers took with them on their trek to the Orange Free State, Natal and the Transvaal. The development of this system of defence is traced back and discussed in detail from its origin to what it !:las become today, emphasizing both the advantages and the problem areas. All aspects of National Service is meticulously attended to, inter alia the role of women and Non-Whites and conculding with the role that immigrants have to fulfil as far as National Service is concerned.